Unlocking the potential of the Lotus River canal as a sustainable public open space - Van, Der Walt Christopher (School of Architecture, Planning and Geomatics, 2023)
Public open spaces are major environmental, social and economic resource, but, these spaces are depleting at an alarming rate and are often undervalued (Cilliers, 2015). Within a South Africa context there are many challenges that coincide with public open spaces especially in informal settlements and established townships where rapid urbanisation leads to increasing pressure to provide housing which often competes with these spaces (Cilliers et al., 2021). The challenges faced by public open spaces and the importance of protecting them will be explored. This research project lands within Gugulethu Township along the Lotus River canal and aims to explore how this public area along the river can be utilised as a sustainable public open space, designed for all role players within the Gugulethu community. The project seek to discover the role that an urban designer can play in highlighting the potential of such spaces and how urban design interventions can be used improve these open spaces.